Rare Biliary Anatomy in Two Patients Presenting with Biliary Obstruction Diagnosed with ERCP - Gary R May; David S Reid; Noel B Hershfield (Canadian Journal of Gastroenterology)
Anatomic anomalies of the exrrahepatic biliary tree are common and often incidental findings at endoscopic retrograde cholangiopancreatography; however, they rarely complicate therapeutic procedures such as stone extraction. The cases of two patients with biliary obstruction due to stones are presented, who were found to have the cystic duct a rising almost directly from the ampulla. This rare anatomic variant posed problems both in terms of interpretation of the cholangiogram and removal of stones. Therapeutic endoscopists should be aware of this and other anomalies of the biliary tract and of the potential problems faced in both interpretation of the cholangiogram and in therapeutic procedures.